Editorial - Chau, Meng Huat (Journal of Modern Languages, 2020)
Welcome to the second issue of the 2020 volume of the Journal of Modern Languages. Thanks to both an increase in submissions, support from colleagues from around the world,and the diligence and dedication of our Editorial Board members, this is the first time the Journal has published two issues in a single yea r since its inception in 1983. This is a real achievement, especially when the two issues were producedduring a timewhen wewere all physically separatedand had to make massive adjustments of various kinds in response to the challenges created by the COVID-19 pandemic. It is perhaps important to note that the Journal of Modern Languages, like all other scholarly journals, depends on the support of individualsfrom a range of areas in modern language studies. The insightful comments and suggestions of reviewers allow the Journal to maintain the high quality of the articles. The number of submissions we receive for considerationof publication steadily increases each year. As a result, we need more and more external reviewers. If any readers of the Journal would like to be external reviewers, please contact us with an indication of the areas in which you have particular expertise. Finally, we would like to express our thanks to all individuals who havemade the Journal possible. As always, a big thank you to the external reviewers who have found time intheirbusy lives to read and provide helpfulcomments on submissions. Our heartfeltthanks certainly go to all the authors who have shared with us their thoughts and latest research findings. Writing and publishing, as we know, require not only hard work but also the patience and determination to go through the entire revision process. To all readers, we can’t thank you enough for your support and commitment over the years. We hope that you will enjoy reading this and future issues of the Journal of Modern Languages.